Relationship of Family Particulars with Mental Health in Tehran Girls\' Students at Third Grade in the Field of Experimental Sciences - Davoud Shoja'ei-Zadeh; Mahshid Nouri; Amir Houshang Mehryar (University of Social Welfare and Rehabilitation Sciences, 2000)
Objective: Personality development is a complicated phenomenon. Several external and internal factors such as hereditary background, congenital status, events afterbirth, individual differences, positive and negative promoting behaviors, and other cultural and social factors alone or in combination affect individual personality. Based on the theory of psychological analysis, experiences at childhood, especially interaction with parents have an undeniable effect on individual personality in adulthood. The subject of the present study is to investigate the relationship of family particulars with mental health in high school girls' students in Tehran at third grade in the field of experimental sciences. The present study is a case-study and its purpose is to study theories on dissatisfaction of students at disorganized families and its relationship with anxiety, depression, violence, and obsession. Materials & Methods: The study subjects were 80 girl students studying at third grade in field of experimental sciences at Tehran high schools. Half of these students were selected as case group and half of them as control group. The subjects were selected with screening method and the SCL-90 test was used to study hypothesis. Results: The results revealed that there was a significant difference between case and control group. The quality of family relationship had a strong correlation with mental growth of child.   Conclusion: Based on obtained results, the atmosphere around the control group was happier than the case group. The members of the case group usually did not talk about their problems with father.